Pengaruh Lama Penggunaan Smartphone terhadap Tajam Penglihatan dalam Aktivitas Siswa SMA Negeri 1 Wuryantoro Wonogiri - Olivia Nurulita Handayani; Setya Ferywidyastuti; Sri Suharti (EMVIRO Jurnal Ilmiah Penelitian Kesehatan, 2025)
Advances in information technology have led to an increase in the use of smartphones in various learning activities, including among students. This study aims to determine the effect of long term smartphone use on a sharp decline in vision in students of SMA Negeri 1 Wuryantoro, Wonogiri. This study uses an observational analytical approach with a cross sectional design. The population in the study was all grade XII students with a total of 108 respondents, which were taken using saturated sampling techniques. Data collection was carried out through questionnaires and basic vision checks. The results showed that most students used smartphones for more than two hours per day (81.48%) and 67.59% of them experienced eye fatigue. In addition, 36.11% of respondents admitted to experiencing a sharp decrease in vision, while the results of the visual examination strengthened the findings. The identified causative factors include duration of use, visibility, lighting intensity, and lack of eye rest habits. Most students are unaware of prevention methods such as the 20-20-20 rule and rarely have regular eye exams. In conclusion, there is a relationship between the duration of smartphone use and a sharp decrease in vision. Eye health education is needed through socialization, smartphone use timing, and regular vision checks as a preventive effort to maintain students' eye health. This research is expected to be the basis for policy interventions in the school environment to increase awareness of the importance of maintaining eye health from an early age, as well as a reference for further research related to digital health in adolescents.